PREDICTOR SCALE OF UPPER EXTREMITY FUNCTION RECOVERY IN MILITARY TRAUMA OF THE UPPER ARM (OFFER TO USE) - Strafun, Sergiy; Haiovych, Vasyl; Telepenko, Hlib (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Objective. To determine the prognostic value of the extent of damage in military trauma to the upper arm for surgical intervention to improve the results of restoring upper limb function. Methods. A retrospective analysis of 30 cases of military trauma of the upper arm in combatants of the Armed Forces of Ukraine was conducted from the stage of admission to our hospital for treatment until 4 months after surgery. Functional outcomes were assessed using the Oxford Shoulder Score (OSS) scale 4 months after surgery. A previously developed scale was used to predict the recovery of upper limb function after military trauma of the upper arm to predict the consequences of surgery. Results. All 30 patients had a gunshot injury to the upper arm as a result of a shrapnel or bullet wound received during combat missions in the war on the territory of Ukraine. All 30 combatants received qualified medical care, underwent staged surgical interventions and a course of rehabilitation recovery. Based on the data of a retrospective analysis of patients, the correlation of rehabilitation results according to the OSS scale and the results of the assessment according to the scale-predictor of recovery of upper limb function in case of gunshot injury to the upper arm is traced. Conclusions. The results obtained after the assessment using the predictor scale serve as an aid in deciding on the feasibility and scope of surgical intervention. The decisive factor is the professionalism of the doctor and the patient's willingness to take risks to restore limb function in severe injuries of the upper arm in a large scope of trauma.